ANALISIS DIPARITAS PENDAPATAN ANTAR WILAYAH DI PROVINSI KALIMANTAN BARAT - B61110037, TIAN SANDU ARISTA (Jurnal Ekonomi Daerah (JEDA), 2016)
The study aims to determine how much the revenue of disparty between district/province in West Kalimantan, examine, and analyze the effect of the primary sector of GDP, secondary sector of GDP, and tertiary sector of GDP and index of Human Development toward the income disparities in West Kalimantan. The data used is secondary data from the published BPS in West Kalimantan, BAPPEDA, and other sources related to the study. The data is analyzed by using an index theil and multiple reggresion of the data panel from 14 districts/province in West Kalimantan in 2008-2012. The result of the study shows the income disparity in West Kalimantan is still relatively small which is the number increasing from 2008 to 2012. According to the analyis conducted by the GDP, primary sector has a significant negative effect due to the primary sector of GDP is a basis sector in most areas of the district/city in West kalimantan which has a role in absorbing the greater labor compared to any other sectors. The secondary sector of GDP has positive and significant effect due to the secondary sector is only owned by a small portion of district/city in West Kalimantan and have greater production output compared to the primary sector. However, this sector is less able to absorb the amount of labour. Secondary sector GDP Â has a positive and negative effect due to the secondary sector GDP is only owned by Regency / City in West Kalimantan and have a higher production output as compared with the primary sector.However this sector is less able to absorb the workforce. GDP tertiary sector has a positive and significant effect due to the tertiary sector GDP is able to provide the greatest production output is compared to other sectors, other than that this sector can absorb greater of jobs than the secondary sector of GDP due to specific work of human labor which cannot be replaced. Human Development Index takes significant negative effect, it is because the increasing HDI index will give the quality of human resources so that it makes the workplace more productive and higher to seize the opportunities. Keyword: disparity, theil index, GDP sectoral, IPM